Retroperitoneal Spinal Extradural Arachnoid Cyst Combined with Congenital Hemivertebrae - Park, Se-Hwan (The Korean Neurosurgical Society, 2012)
Spinal extradural arachnoid cysts usually cause symptoms related to spinal cord or nerve root compression. Here, we report an atypical presentation of a spinal extradural arachnoid cyst combined with congenital hemivertebra which was presented as a retroperitoneal mass that exerted mass effects to the abdominal organs. On image studies, the communication between the cystic pedicle and the spinal arachnoid space was indistinct. Based on our experience and the literature of the pathogenesis, we planned anterior approach for removal of the arachnoid cyst in order to focus on mass removal rather than ligation of the fistulous channel. In our estimation this was feasible considering radiologic findings and also essential for the symptom relief. The cyst was totally removed with the clogged 'thecal sac-side' end of the cystic pedicle. The patient was free of abdominal discomfort by one month after the surgery.